Asesmen - Suryo Nugroho Markus; Laili Rahmatul Ilmi; Praptana Praptana; Sis Wuryanto; Heri Herawan; Sujono Riyadi; Tri Sunarsih (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
a complete medical record reflects the quality of good documentation, the complete of diagnosis writing reduces incorrect and inaccurate code and appropriate reporting to support decision makers. this study aims to measure the completeness and accuracy of the death code and the basic cause of death of patients. This study uses a quantitative descriptive design using a completeness checklist instrument. researchers used secondary data from the medical records of patients who died in 2021, the total sample was 199 using the slovin formula. secondary data analyzed with STATA, presented with tabulations and descriptive narratives. the basic cause of the basic cause of death was highest in code J80 at 33 (17%), J12.8 at 21 (11%) and the third being E11.9 . Based on the category of completeness of filling out of the 199 medical records analyzed, there were 37% (75) death forms that were not filled in completely